Effects of Morinda citrifolia L. leaf extract on human T- lymphoblatic leukemia (JURKAT) cell and WEHI-3B cell- induced murine leukemia - Ahmadi, Negin (2016)
Morinda citrifolia (Rubiaceae) or mengkudu is familiarly known as Ba JiTian, Noni or Nonu, Indian Mulberry, Nhau and Cheese fruit. There has been no literature reported on the mechanism of Morinda citrifolia leaf extract and its effects on leukemia. Therefore, the anti-leukemic effect of Morinda citrifolia leaf extract was examined on a human T- lymphoblastic leukemia (JURKAT) cells line and on WEHI-3B (myelomonocytic leukaemia) cell-induced murine leukemia. MTT assay, fluorescent microscope, flow cytometric analysis after Annexin V-FITC staining, cell cycle, TUNEL assay, and caspase-3, -8 and -9 assays were employed. The study showed that Morinda citrifolia leaf extract significantly (P<0.05) suppressed proliferation of JURKAT and WEHI-3B cells in vitro in a time-dependent manner with an IC50 of 14.5 ± 0.1 and 17.05 ± 0.14 μg/ml at 72 hours. The anti-proliferative effect of Morinda citrifolia leaf extract on JURKAT and WEHI-3B cells was shown to induce apoptosis via extrinsic pathway. The study also attempts to determine the effect of Morinda citrifolia leaf extract and Zerumbone on WEHI-3B cells. The results show that exposure of WEHI-3B cells to Morinda citrifolia leaf extract along with Zerumbone caused a greater level of cell progress inhibition than either extract alone. BALB/c mice were leukemia-induced with a single intraperitoneal injection of WEHI-3B cells (1×106 cells/animal). The in vivo study revealed that oral Morinda citrifolia leaf extract at doses of 100 mg/kg and 200 mg/kg suppressed the proliferation of leukemic cells in leukemic mice by the decrease in leukemic cell population in the spleen. Histopathologic, electron microscopic, immunochemical evaluations and TUNEL assay studies showed the Morinda citrifolia leaf extract leukemia suppression is via apoptosis. To determine whether the leukaemia was restricted to the peritoneal cavity, this study evaluated whether i.p. inoculated WEHI-3 cells were able to migrate to the bone marrow. It is observed that WEHI-3 cells were present in the marrow of inoculated mice as early as 24 h post-inoculation, demonstrating the ability of these cells to colonise secondary sites. This observation demonstrates their aggressive nature, which resulted in the mortality of all animals tested within 30 days. By contrast, under identical conditions, Morinda citrifolia leaf extract markedly promotes the proliferation of mouse normal mononuclear bone marrow cells. Using qRT-PCR Array, on the spleen cells of Morinda citrifolia leaf extract treated leukemic mice indicated the molecular mechanisms accountable for the effective treatment included anti-inflammatory and immune-modulating responses, JAK-STAT signaling, and hematopoiesis pathways. To define potential toxicity of Morinda citrifolia leaf extract, human peripheral blood mononuclear cells (PBMC) were treated in vitro with serial concentrations of Morinda citrifolia leaf extract up to 100 μg/mL and normal BALB/c mice treated orally with Morinda citrifolia leaf extract at doses up to 200 mg/kg. The treatment did not produce any sign of toxicity in either normal human peripheral mononuclear cells or mice at any of the doses used, indicating that Morinda citrifolia leaf extract is safe for parenteral use. In conclusion, the Morinda citrifolia leaf extract, inhibited the proliferation of leukemia in vitro and in vivo leading to the programmed cell death. The in vivo study on a zenographic leukemia BALB/c mice model clearly shows that Morinda citrifolia leaf extract inhibited the proliferation of leukemia via the induction of apoptosis and other signal transduction pathways.